Highly Unequal Three-Port Power Divider: Theory and Implementation - Duolong Wu; Adriana Serban; Magnus Karlsson; Shaofang Gong (International Journal of Antennas and Propagation)
A three-port power divider consisting of a directional coupler, a Wilkinson power divider, and two transmission lines connected to them is proposed. Theoretical analysis reveals that highly unequal power division can be achieved by a feedback mechanism of two transmission lines along with the coupling coefficient of the directional coupler and the power division ratio of the Wilkinson power divider. The three-port power divider inherits the performance characteristics of high isolation, low reflection coefficients at all ports, and the minimum number of components. The proposed power divider is designed at 5.8 GHz and fabricated and evaluated through measurements. It demonstrates that electromagnetic simulation results are in good agreement with theoretical prediction and measurement results. The three-port power divider is compact in the planar form, so it can be easily integrated into radio frequency front ends.